Techno-economic evaluation of using biomass-fired auxiliary units for supplying energy requirements of CO2 capture in coal-fired power plants. (January 2015) - Khorshidi, Zakieh; Ho, Minh T.; Wiley, Dianne E.
Highlights: Investigate various biomass auxiliary units to provide energy for CO2 capture. Evaluate the trade-offs between performance and economics of auxiliary units. Examine the economic viability under different fuel prices and incentive schemes. Abstract: Parasitically providing the energy required for CO2 capture from retrofitted coal power plants can lead to a significant loss in output of electricity. In this study, different configurations of auxiliary units are investigated to partially or totally meet the energy requirements for MEA post-combustion capture in a 500 MW sub-critical coal-fired plant. The auxiliary unit is either a boiler, providing only the heat required for solvent regeneration in the capture process or a combined heat and power (CHP) unit, providing both heat and electricity. Using biomass in auxiliary units, the grid loss is reduced without increasing fossil fuel consumption. The results show that using a biomass CHP unit is more favourable than using a biomass boiler both in terms of CO2 emission reductions and power plant economic viability. By using an auxiliary biomass CHP unit, both the emission intensity and the cost of electricity would be marginally lower than for a coal plant with capture. Further emission reductions occur if CO2 is captured both from the coal plant and the auxiliary biomass CHP, resulting in negative emissions. However, high incentive schemes (a carbon price higher than 55 /t CO2 or a combination of lower carbon price and renewable energy certificates) or a low biomass price (lower than 1 /GJ) are required to make CO2 capture from both the coal plant and the auxiliary biomass CHP unit economically attractive. All cost comparisons are for CO2 capture only and CO2 transport and storage are not included in this study.